2016
DOI: 10.1155/2016/4626027
|View full text |Cite
|
Sign up to set email alerts
|

The Prognosis of Cardiac Origin and Noncardiac Origin in-Hospital Cardiac Arrest Occurring during Night Shifts

Abstract: Background. The survival rates of in-hospital cardiac arrests (IHCAs) are reportedly low at night, but the difference between the survival rates of cardiac origin and noncardiac origin IHCAs occurring at night remains unclear. Methods. Outcomes of IHCAs during different shifts (night, day, and evening) were compared and stratified according to the etiology (cardiac and noncardiac origin). Result. The rate of return of spontaneous circulation (ROSC) was 24.7% lower for cardiac origin IHCA and 19.4% lower for no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Previous studies have reported that hospitals tend to attend to patients with a greater severity of illness at night; hence, the in-hospital CPR conducted during the night yielded lower ROSC rates [ 10 ]. Further, because these studies [ 11 , 12 ] analyzed the nighttime or weekend effects within the same CPR system, it is likely that patient-related factors and fatigue levels of the medical staff contributed to the lower ROSC rates.. In our study, it is unlikely that severity of illness contributed to the differences in the CPR outcomes; this is supported by the non-significant differences in the Charlson comorbidity scores between the three teams.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have reported that hospitals tend to attend to patients with a greater severity of illness at night; hence, the in-hospital CPR conducted during the night yielded lower ROSC rates [ 10 ]. Further, because these studies [ 11 , 12 ] analyzed the nighttime or weekend effects within the same CPR system, it is likely that patient-related factors and fatigue levels of the medical staff contributed to the lower ROSC rates.. In our study, it is unlikely that severity of illness contributed to the differences in the CPR outcomes; this is supported by the non-significant differences in the Charlson comorbidity scores between the three teams.…”
Section: Discussionmentioning
confidence: 61%
“…Our findings are similar to those from previous studies, which showed that patients were more likely to require CPR and were more likely to experience the poorest outcomes during the night. [ 16 , 17 ] In addition, the ROSC rate of CPR did not vary across seasons or years but did vary by time of day. A previous study [ 17 ] showed that the ROSC rates were lower during the night than during the day for both cardiac and respiratory arrest.…”
Section: Discussionmentioning
confidence: 98%
“…[ 16 , 17 ] In addition, the ROSC rate of CPR did not vary across seasons or years but did vary by time of day. A previous study [ 17 ] showed that the ROSC rates were lower during the night than during the day for both cardiac and respiratory arrest. Furthermore, ROSC rates were lower for CPR performed on Sundays and for female patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is similar with the study conducted in Brazil which showed that 70.5% of cardiac arrest patients are over 40 years old and 29,5% of cardiac arrest patients are less than or equal to 40 years old. 9,10 This can occur because by increasing the patient's age, the risk of experiencing comorbid diseases or terminal diseases is also getting bigger. 1,11 Statistically, the patient's age did not show a significant difference towards outcome in cardiac arrest patients.…”
Section: Discussionmentioning
confidence: 99%